Regulating the employment relationship in Europe : a guide to Recommendation No. 198 : European Labour Law Network (ELLN). (International Labour Organization, 2013)
This study is the result of a strategic partnership between the ILO and the European Labour Law Network (ELLN) to produce an updated version of the guide to Recommendation No. 198, with a specific focus on European countries.